Tuning p-type to n-type semiconductor nature by charge transfer cocrystallization: effect of transfer integral vs. reorganization energy. Issue 11 (21st February 2022) - Mandal, Arkalekha
Abstract : A p-type semiconductor di-carbazole donor is co-crystallized with a TCNQ acceptor to form a 1 : 2 cocrystal, and the resulting charge transfer cocrystal exhibits n-type semiconductor nature. Abstract : In this contribution, a 1 : 2 mixed stack (⋯DADA⋯ arrangement) donor acceptor cocrystal comprising the hole transport material CBP (4, 4′-bis(9 H -carbazole-9-yl)biphenyl) as the donor (D) and TCNQ (7, 7′, 8, 8′-tetracyano-1, 4-quinodimethane) as the acceptor (A) was synthesized by the green method of mechano-chemical cocrystallization. Theoretical calculations predict n-type nature in the CBP:(TCNQ)2 cocrystal, which possesses a low band-gap (0.94 eV) with a stable LUMO energy (−4.49 eV), while the predominant hole transport nature of the donor CBP possessing a HOMO level (−5.31 eV) is reported. The switching of the p-type semiconductor nature of the donor CBP to the n-type nature in the CBP:(TCNQ)2 cocrystal has been elucidated in terms of two parameters of the charge transfer process, viz., charge transfer integral and reorganization energy, along with the frontier MO energy level. The role of the molecular structure of CBP, as well as the crystal packing to dictate the charge carrier property, is studied. Thus, the mechano-chemical charge transfer cocrystallization can be compared with heteroatom doping in silicon-based semiconductors to attain a switching of the polarity.